Social Embeddedness of Pro-Environment Fisherman Community in The Use of Eco-Friendly Fishing Gear Technology at Drini Beach Gunung Kidul Yogyakarta - Marini Kristina Situmeang; Yulius Slamet; Drajat Tri Kartono (Research and Community Services Institutes of Udayana University, 2017)
This study aims to determine to what extent the knowledge of the fishing communities of Gunung Kidul Yogyakarta in interpreting the use of environmentally friendly fishing technology. Also, to analyze how the form of social embeddedness related to the conservation of environmentally friendly fishing gear is seen from the dimensions of relational relationships and structural relationships in the context of social networks Coastal fishermen community Drini Gunung Kidul Yogyakarta. This study uses the sociology theory of economics from Granovetter on Social Embeddedness in